Rapid Prototyping for the Formulation of Monolith and Membrane for CO2 Removal - Lai, L.S. (Taylor and Francis Ltd., 2021)
Sequestration of CO2 is crucial to prevent further worsening of the environmental impact caused by global warming. Monoliths and membranes made from polymeric and inorganic materials have been used for CO2 removal to address environmental issues. Rapid prototyping technology offers a great potential for the fabrication of monoliths and membranes with high flexibility in terms of geometry and structure. This paper reviews the potential of the monolith and membrane fabricated through rapid prototyping for CO2 removal. The printing mechanism, chemical composition used in the fabrication of monoliths and membranes, as well as their CO2 removal capability are reviewed. The potential of monoliths and membranes is expected to be maximized for CO2 removal with the high flexibility in tailoring the geometry, surface area and associated with the fast growth of rapid prototyping technology. Â© 2021 Taylor & Francis Group, LLC.